Design of threshold voltage insensitive pixel driver circuitry using a-IGZO TFT for AMOLED displays. (July 2020) - Sodhani, Aditya; Kandpal, Kavindra
Abstract: This work proposes a novel amorphous-indium-gallium-zinc-oxide thin film transistor (a-IGZO TFT) based pixel driver circuitry to compensate for threshold voltage variations of TFTs and OLED current degradations for AMOLED (Active Matrix Organic Light-Emitting Diodes) displays. The proposed circuit uses a three-phase clocking scheme i.e. threshold voltage detection phase, data input phase and emission phase for compensating threshold voltage variations. The circuit has been simulated and verified with cadence spectre using a-IGZO TFT and OLED SPICE models. The proposed circuit is able to maintain the OLED current with a maximum error of 0.68% when the threshold voltage is varied from −3.5 ​V to 3.5 ​V.